The effects of profit-sharing distributions on employee stock purchase plan participation - Jan C. Hennig; Rieke Hullmann; Holger A. Rau; Michael Wolff (Frontiers in Behavioral Economics)
IntroductionFirms use various forms of equity-based compensation to allow employees to participate in their success.MethodsWe examine how an unannounced profit-sharing distribution (PSD) affects participation in Employee stock purchase plans (ESPPs), which offer discounted shares. Using panel data from a multinational firm, we find counterbalancing effects of the PSD.ResultsWhile it attracts new participants to the ESPP, a similar share of former participants exit the program after receiving the distribution. This latter effect is particularly pronounced in countries characterized by higher average levels of prosociality.DiscussionOur findings suggest that unexpected profit sharing can have heterogeneous effects on ESPP participation across different cultural contexts.